The Effect of Information Technology Application on Organizational Performance Through Cross Functional Team and Total Quality Management Implementation - Tommy Westonlie; Hotlan Siagian; Zeplin Jiwa Husada Tarigan (Master of Management, School of Business and Management, Petra Christian University, 2018)
In this thesis discuss the effect of Information Technology Application on Organizational Performance through Cross Functional Team and Total Quality Management Implementation on the company. In this study using primary data with 102 population and 50 samples of manufacturing companies using data collection methods, namely 5 points Likert scale in the form of questionnaires distributed in companies that are open or closed that have large and medium industrial groups on firm manufacturing in East Java. This study uses Structural Equation Modeling analysis techniques, also called path modeling with SmartPLS tools. The questionnaire collected was 57 questionnaires. The result showed that the effect of Information Technology Application on Organizational Performance was significant. The results showed that the effect of Information Technology Application on Cross Functional Team was significant, the result showed that the effect of Information Technology Application on Total Quality Management Implementation was significant, the result showed that the effect of Cross-Functional Team on Organizational Performance was significant, the result showed that the effect of Cross-Functional Team on Total Quality Management Implementation was significant and the result showed that the effect of Total Quality Management Implementation on Organizational Performance was significant in firms manufacturing in East Java.